The Woven Endobridge as a treatment for acutely ruptured aneurysms: A review of the literature. Issue 5 (October 2021) - Crinnion, William; Bhogal, Pervinder; Makalanda, Hegoda Levansri Dilrukshan; Wong, Ken; Arthur, Adam; Cognard, Christophe; Henkes, Hans; Fiorella, Dave; Pierot, Laurent
The Woven Endobridge (WEB; Microvention, Aliso Viejo, California, USA) is a relatively new device which has been shown to be safe and effective for the treatment of wide necked bifurcation aneurysms in multiple prospective Good Clinical Practice studies. However, the vast majority of aneurysms included in these studies have been unruptured. The aim of this review is to summarise the current evidence available on the treatment of ruptured aneurysms with the WEB.